Expanded programme for immunisation: Review of the Western Cape Department of health public private partnership - Werner, Jesse (Department of Public Health and Family Medicine, 2022)
Background: The demand for healthcare services has been steadily increasing over the years whilst the health system is subjected to increasing resource limitations. The private sector has therefore, in various ways, including Public Private Partnerships, been viewed as a means to address these resource limitations. The Western Cape Department of Health has undertaken to expand the Expanded Programme for Immunisation as a Public Private Partnership. The programme aims to improve population health outcomes through increased vaccination coverage and service access. Benefits and challenges of such partnerships have been identified in various contexts. However, there is a significant research gap pertaining to public partnerships with for-profit entities, particularly in Sub-Saharan Africa. Objectives: The study sought firstly to describe the socio-demographic characteristics of clients who utilised the Expanded Programme for Immunisation public private partnership services in the 2016/17 financial year. Secondly, to compare the socio-demographic characteristics of those using the Expanded Programme for Immunisation public private partnership services to those using the Expanded Programme for Immunisation services in Western Cape public sector facilities. Thirdly to describe the proportion of Expanded Programme for Immunisation public private partnership clients who have utilised public sector facilities for healthcare in the Western Cape. Finally, to describe the provincial health staff experiences of the service. Methods: A descriptive quantitative cross sectional study and 12 semi- structured interviews were undertaken to fulfill the objectives of the study. The study population was clients who utilised the Western Cape Department of Health Expanded Programme for Immunisation services from April 2016 to March 2017 in the Western Cape Province. Convenience sampling of public private partnership clients was conducted which enabled the descriptive analysis whilst a random sample of public sector immunisation clients enabled the socio-economic status comparison to the public private partnership clients. Socio-economic status was analysed by reviewing the annual head of household income of clients estimated by client postal code. Western Cape Government staff were selected for interviews to gain insights into provinical staff experiences of the partnership. This was conducted by snowball sampling methods. Univariate analysis was conducted on data submitted by 80 private partners and thematic coding was used to analyse the staff interviews. Results: The proportion of provincial Expanded Programme for Immunisation client visits attributable to the public private partnerships was approximately 12% in 2016/17. The 80 participating private partners provided almost 60, 000 vaccinations to 23,695 clients in the period of a year. The public private partnership appears to be accessed by users who are of similar socioeconomic status to the Expanded Programme for Immunisation clients accessing public sector facilities. Additionally, the small proportion (12.2%) of public private partnership clients having access to medical insurance further supports the findings of the similar socioeconomic profile of the two groups. 42.7% of public private partnership clients were found to have visited public sector facilities therefore suggesting that in the absence of the public private partnership they might otherwise have utilised the public sector to attain the service. Notwithstanding concerns around management and governance, the initiative is generally appreciated and supported by government stakeholders. Conclusions and recommendations: The Western Cape Department of Health Expanded Programme for Immunisation public private partnerships operate at a scale that accounts for a meaningful proportion of the immunisation coverage and is utilised by clients of similar socioeconomic status when compared to Expanded Programme for Immunisation clients accessing public sector facilities. The small proportion of public private partnership clients having access to medical insurance suggests public private partnership clients might otherwise have utilised the public sector in the absence of the partnership. Overall, the public private partnership has been appreciated by the Western Cape Department of Health staff and affords clients a degree of financial risk protection. Future research areas include an economic evaluation, a benefits incidence analysis and the describing barriers to uptake of the service from the perspective of stakeholders external to the Western Cape Department of Health.